Evaluating the Efficiency of Teacher Technology Competence on Student Achievement: A Data Envelopment Analysis (DEA) Approach - Sabariah, Sabariah; Rufi’i, Rufi’i; Bandono, Adi; Sailin, Siti Nazuar; Sembiring, Hendra Syah Putra (STAI Publisistik Thawalib Jakarta, 2026)
Indonesia’s low ranking in human resource competitiveness among ASEAN countries highlights the urgency to improve educational quality through effective teacher competency development, particularly in technology integration. This study aims to analyze the efficiency of teachers' technological competence development in improving students' learning achievement at Cita Hati schools in Surabaya using the Data Envelopment Analysis (DEA) approach. The research was conducted across three school levels: elementary, junior high, and senior high, under the Cita Hati Foundation, using secondary data from 2019 to 2023. Inputs included teacher training, digital infrastructure, and technology investment, while outputs were measured by student achievement. The DEA Constant Returns to Scale (CRS) model was used, with data processed through Python. The results show that the elementary and senior high schools consistently achieved maximum efficiency (1.0), while the junior high school demonstrated inefficiency, particularly from 2021 to 2023, with scores exceeding 1.0. However, a gradual improvement in efficiency was observed toward 2023. Forecasts indicate potential efficiency improvement for junior high, though uncertainty remains. Conclusion: the study implies that strategic teacher development and targeted investment can improve educational outcomes. The findings contribute to institutional decision-making and policy formulation regarding technology-based teacher development programs.